Cynometra cauliflora essential oils loaded-chitosan nanoparticles: Evaluations of their antioxidant, antimicrobial and cytotoxic activities - Benedict, Samling; Zaini, Assim; Woei-Yenn, Tong; Chean-Ring, Leong; Syarifah, Ab Rashid; Nik Nur Syazni, Nik Mohamed Kamal; Musthahimah, Muhamad; Wen-Nee, Tan (International Journal of Biological Macromolecules, 2022)
Nanoencapsulation has appeared as an alternative approach to protect the bioactive constituents of essential oils (EOs) and to improve their properties. In this study, Cynometra cauliflora essential oils (CCEOs) were nanoencapsulated in chitosan nanoparticles (CSNPs) using an emulsion-ionic gelation technique. Transmission electron microscopy (TEM) images illustrated a well dispersion and spherical shape of C. cauliflora EOs-loaded chitosan nanoparticles (CCEOs-CSNPs) with an average size of less than 100 nm. In addition to that, Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS) and X-ray diffraction (XRD) analyses revealed the success of CCEOs nanoencapsulation. The encapsulation efficiency (EE) was in the range of 38.83% to 44.16% while the loading capacity (LC) reached 32.55% to 33.73%. The antioxidant activity (IC50) of CCEOs-CSNPs was ranged from 21.65 to 259.13 μg/mL when assessed using DPPH radical scavenging assay. CCEOs-CSNPs showed an appreciable antimicrobial effects on diabetic wound microorganisms. Notably, cytotoxic effects against human breast cancer MCF-7 and MDA-MB-231 cells recorded IC50 of 3.72–17.81 μg/mL and 16.24–17.65 μg/mL, respectively, after 72 h treatment. Interestingly, no cytotoxicity against human breast normal MCF-10A cells was observed. Thus, nanoencapsulation using CSNPs could improve the properties of CCEOs in biomedical related applications.